2002
DOI: 10.1007/s12134-002-1001-z
|View full text |Cite
|
Sign up to set email alerts
|

Immigrant concentration and educational attainment: Evidence from US data

Abstract: Ninety-five percent of the 30 million foreign-born persons living in the UnitedStates reside in a metropolitan area, and more than one half reside in just six gateway cities. We investigate whether less-educated immigrants tend to settle in large urban communities of their compatriots. Based on statistical analysis we find a negative relationship between the level of education and the size of immigrant population for the immigrants born in China, India, Philippines, Korea, El Salvador, Cuba, and Mexico. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2006
2006

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…More detailed investigation of the location choice of immigrants from different countries has found that the better-educated immigrants tend to disperse more widely than their less-educated compatriots. Presumably higher education In the 1990s, this pattern was not as distinct as in the 1970s and 1980s since relatively more immigrants started to settle in inland cities and states (see, for example, Camarota and Keeley, 2001;Fix, Zimmerman, and Passel, 2001). allows new immigrants to be less dependent upon the safety networks provided by ethnic communities (see Bartel, 1989;Dunlevy, 1991;Kritz and Nogle, 1994;Newbold, 1996Newbold, , 1999Zavodny, 1998;Frey and DeVol, 2000;Jaeger 2000;Izyumov et al 2002). It has been further established that the secondary migration of foreign-born persons does not deviate from this pattern of settlement and, if anything, reinforces it.…”
Section: Determinants Of Migrationmentioning
confidence: 99%
See 2 more Smart Citations
“…More detailed investigation of the location choice of immigrants from different countries has found that the better-educated immigrants tend to disperse more widely than their less-educated compatriots. Presumably higher education In the 1990s, this pattern was not as distinct as in the 1970s and 1980s since relatively more immigrants started to settle in inland cities and states (see, for example, Camarota and Keeley, 2001;Fix, Zimmerman, and Passel, 2001). allows new immigrants to be less dependent upon the safety networks provided by ethnic communities (see Bartel, 1989;Dunlevy, 1991;Kritz and Nogle, 1994;Newbold, 1996Newbold, , 1999Zavodny, 1998;Frey and DeVol, 2000;Jaeger 2000;Izyumov et al 2002). It has been further established that the secondary migration of foreign-born persons does not deviate from this pattern of settlement and, if anything, reinforces it.…”
Section: Determinants Of Migrationmentioning
confidence: 99%
“…However, the total number of immigrants of the same nationality seem to capture the ''ethnic networks'' effect fairly well. Izyumov et al (2002) show that the number of foreign-born persons in a metro is a good proxy for enclaves, as a majority of new immigrants from most countries live in a small number of postal zip codes of the major gateway cities of the United States. In Chicago, for example, 47 percent of Chinese immigrants reported residence in but 10 of the metros' 381 zip codes.…”
Section: Data and Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Network effects have also been subject to special scrutiny in the migration context as they are seen as alleviating migration costs (Bartel, 1989, Zimmermann, 1996 or improving employment and/or wage opportunities for newcomers (Gross and Schmitt, 2003). 3 Note that Izyumov et. al.…”
mentioning
confidence: 99%